Accurate Fault Location Technology of Cable Head in Switchgear based on Phase-based CT and Zero-Sequence CT. Issue 1 (1st April 2022) - Zhang, Lihua; Wang, Tie; Gu, Yadong; Yang, Guodong; Wang, Chenguang
Abstract: The fault location technology for single-phase grounding fault of line has been mature, but there is little research on cable head in switchgear using this technology. Because the grounding line selection device cannot effectively identify and locate the single-phase grounding fault of the cable head in the switchgear, a cable head fault model is established. The synthetic zero-sequence current signal of three-phase CT and the zero-sequence current signal of zero-sequence CT are decomposed by variational mode decomposition (VMD). The grey correlation degree is then calculated to analyze the similarity of the two signals. Thus, the precise fault location technology of cable head in switchgear based on the measurement of phase CT and zero-sequence CT is proposed, and the correctness and feasibility of the proposed technology are verified by ATP simulation software.